Tiktok Social Media On Students' Mathematical Understanding Ability - Cut Latifah Zahari; Syah witri witri (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
The existence of various social media platforms is a result of globalization as it is practiced today. One of the most famous social media platforms is Media TikTok. On social media TikTok, there are various videos. There are lots of educational videos available besides being fun. This has a significant impact on students' mathematical understanding abilities. This study seeks to ascertain the extent to which the social media platform TikTok affects students' math comprehension skills at SMP Negeri Bandar Khalipah sub-district. Associative research is used in this type of research along with quantitative strategies. the one-shot case study design. and pre-experimental methodology used in this study. The research population was 225 class VII students of public junior high schools in the Bandar Khalipah sub-district 2021-2022. All students of SMPN 1 and SMPN 2 with the selected classes VII-1 and VII-2, totaling 50 students, were sampled from Bandar Khalipah District. Test instruments and questionnaires were used to obtain data. Based on the results of data analysis, it is known that social media TikTok has a positive effect of 45% on students' mathematical understanding abilities at SMP Negeri Bandar Khalipah Subdistrict, and has an effect of 87.25% for SMP Negeri 1 and 87.75% for SMP Negeri 2, respectively based on the average score of math items. This shows that the average value of the two school items is quite high.